Helicobacter monodelphidis sp. nov. and Helicobacter didelphidarum sp. nov., isolated from grey short-tailed opossums (Monodelphis domestica) with endemic cloacal prolapses. Issue 12 (20th December 2020) - Shen, Zeli; Mannion, Anthony; Lin, Maggie; Esmail, Michael; Bakthavatchalu, Vasudevan; Yang, Stephanie; Ho, Calvin; Feng, Yan; Smith, Briony; Elliott, James; Gresham, Vince; VandeBerg, John L.; et al.
Abstract : In a search for potential causes of increased prolapse incidence in grey short-tailed opossum colonies, samples from the gastrointestinal tracts of 94 clinically normal opossums with rectal prolapses were screened for Helicobacter species by culture and PCR. Forty strains of two novel Helicobacter species which differed from the established Helicobacter taxa were isolated from opossums with and without prolapses. One of the Helicobacter species was spiral-shaped and urease-negative whereas the other Helicobacter strain had fusiform morphology with periplasmic fibres and was urease-positive. 16S rRNA gene sequence analysis revealed that all the isolates had over 99 % sequence identity with each other, and were most closely related to Helicobacter canadensis . Strains from the two novel Helicobacter species were subjected to gyrB and hsp60 gene and whole genome sequence analyses. These two novel Helicobacter species formed separate phylogenetic clades, divergent from other known Helicobacter species. The bacteria were confirmed as novel Helicobacter species based on digital DNA–DNA hybridization and average nucleotide identity analysis of their genomes, for which we propose the names Helicobacter monodelphidis sp. nov. with the type strain MIT 15-1451 T (=LMG 29780 T =NCTC 14189 T ) and Helicobacter didelphidarum sp. nov with type strain MIT 17-337 T (=LMG 31024 T =NCTC 14188 T )